If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 38 = 2(x + 10) + 4 Reorder the terms: 38 + x = 2(x + 10) + 4 Reorder the terms: 38 + x = 2(10 + x) + 4 38 + x = (10 * 2 + x * 2) + 4 38 + x = (20 + 2x) + 4 Reorder the terms: 38 + x = 20 + 4 + 2x Combine like terms: 20 + 4 = 24 38 + x = 24 + 2x Solving 38 + x = 24 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 38 + x + -2x = 24 + 2x + -2x Combine like terms: x + -2x = -1x 38 + -1x = 24 + 2x + -2x Combine like terms: 2x + -2x = 0 38 + -1x = 24 + 0 38 + -1x = 24 Add '-38' to each side of the equation. 38 + -38 + -1x = 24 + -38 Combine like terms: 38 + -38 = 0 0 + -1x = 24 + -38 -1x = 24 + -38 Combine like terms: 24 + -38 = -14 -1x = -14 Divide each side by '-1'. x = 14 Simplifying x = 14
| 72x-44=45 | | 16=u/2 | | 0.06+2(0.07x-1)=2 | | 8x+8x+8x=143 | | -8=5n | | 7X+6x-3x-5=25 | | 10(x+2)=4(x-1) | | x^2-31x+130=0 | | 10-32=56 | | 266=-14a | | x+5y=6x+15 | | 8p=-4 | | -11+-5+-4= | | 2(x-3)-10=14 | | 72+n=78 | | -(-5/3x3) | | 30=15z | | X+18=3(2x+1) | | 7(2+3x)+12= | | 6h-3.7h= | | (9+6n)+(-5+9m)= | | N*-3+8=20 | | 5x^2-28=17 | | 3(x+4)+12=48 | | -4a-2(-6a+2)=-22 | | 7(-10-3x)=-28 | | -k^4+3k^3+9k^2+5k=0 | | -4+3y=4 | | 27=6(x-2) | | 2(d+1)=-75 | | 8(x-9)-9(x-8)=x+7-(x-1) | | 2x+2=-38-2x |